Source Contributions to Carbon Monoxide Concentrations During KORUS‐AQ Based on CAM‐chem Model Applications. Issue 5 (7th March 2019) - Tang, Wenfu; Emmons, Louisa K.; Arellano Jr, Avelino F.; Gaubert, Benjamin; Knote, Christoph; Tilmes, Simone; Buchholz, Rebecca R.; Pfister, Gabriele G.; Diskin, Glenn S.; Blake, Donald R.; Blake, Nicola J.; Meinardi, Simone; et al.
Abstract: We investigate regional sources contributing to CO during the Korea United States Air Quality (KORUS‐AQ) campaign conducted over Korea (1 May to 10 June 2016) using 17 tagged CO simulations from the Community Atmosphere Model with chemistry (CAM‐chem). The simulations use three spatial resolutions, three anthropogenic emission inventories, two meteorological fields, and nine emission scenarios. These simulations are evaluated against measurements from the DC‐8 aircraft and Measurements Of Pollution In The Troposphere (MOPITT). Results show that simulations using bottom‐up emissions are consistently lower (bias: −34 to −39%) and poorer performing (Taylor skill: 0.38–0.61) than simulations using alternative anthropogenic emissions (bias: −6 to −33%; Taylor skill: 0.48–0.86), particularly for enhanced Asian CO and volatile organic compound (VOC) emission scenarios, suggesting underestimation in modeled CO background and emissions in the region. The ranges of source contributions to modeled CO along DC‐8 aircraft from Korea and southern (90°E to 123°E, 20°N to 29°N), middle (90°E to 123°E, 29°N to 38.5°N), and northern (90°E to 131.5°E, 38.5°N to 45°N) East Asia (EA) are 6–13%, 5%, 16–28%, and 9–18%, respectively. CO emissions from middle and northern EA can reach Korea via transport within the boundary layer, whereas those from southern EA are transported to Korea mainly through the free troposphere. Emission contributions from middle EA dominate during continental outflow events (29–51%), while Korean emissions play an overall more important role for ground sites (up to 25–49%) and plumes within the boundary layer (up to 25–44%) in Korea. Finally, comparisons with four other source contribution approaches (FLEXPART 9.1 back trajectory calculations driven by Weather Research and Forecasting (WRF) WRF inert tracer, China signature VOCs, and CO to CO2 enhancement ratios) show general consistency with CAM‐chem. Key Points: Korean sources contribute 6‐13% to CO along DC‐8 flight tracks, while contributions of different East Asian subregions vary from 5% to 28% Middle East Asian sources dominate (up to 64%) continental outflows to Korea, but Korean emissions are more important for CO near surface Contributions using CAM‐chem tags agree with FLEXPART‐WRF back trajectories, WRF NO2 inert tracers, China signature VOCs, and CO/CO2